حکمران کی معزولی: سیاستِ شرعیہ کی روشنی میں ایک تحقیقی مطالعہ: The Dethronement of the Ruler: A Critical Study in the view of Islamic Jurists (Al-Aasar, 2025)
This research is based on the critical analysis of the ruler and his obligations during his governance. It highlights the Islamic perspective and worldview in the light of Islamic jurisprudential Principles. In the context of Islamic teachings, the ruler is not entitled to his power only, but he must practically apply them in society by practicing justice, Islamic punishments, better governance for people, and the protection of their rights. Moreover, when the ruler does not fulfill his duties and responsibilities accordingly and is found to any negligent, the Islamic Sharia may call for his dismissal from power. In this research paper, the views of Islamic jurists have been critically and comparatively discussed. Whereas the reasons of his dismissal in negligence to ethical, mental, physical are explained in view of various scholars of Islamic Shariah and jurisprudence in detail. The political system and the forms of democracy in modernism and post-modernism have also been critically analyzed. This research concludes that the removal of a ruler is permissible and in some serious issues it becomes an obligation. This study is an attempt to provide the Muslim Ummah with political guidance, intellectual wisdom, and Sharia-based discussions so that the requirements of justice and Sharia in governance shall be practically applied in the community.